ANALISIS KANDUNGAN LOGAM DALAM LIPSTIK MELALUI SPEKTROFOTOMETRI UV-VIS - Sari Rahmiati; Vitri Aprilla Handayani; Nadia Sabrina; Mulyono Mulyono; Herpina Okti (Jurusan Kimia FMIPA Universitas Lampung, 2023)
Cosmetics have become one of the most sought-after aspects for women today. One commonly used cosmetic product is lipstick, which is used to add color to the lips. This research aims to identify the presence of heavy metals in lipstick samples. The study encompasses two types of tests: qualitative and quantitative analysis of metal content in lipstick. The qualitative test aims to determine whether lipstick contains certain metals using simple reagents. Meanwhile, the quantitative test, involving the use of a UV-VIS spectrophotometer, is conducted to determine the concentration of metals that produced a positive result in the qualitative test. The qualitative test results indicate that the lipstick sample contains iron (Fe) as it exhibits a red color change. The quantitative test results reveal that the concentration of Fe in the lipstick is 6.0034 mg/kg, exceeding the recommended threshold set by the Department of Health (Depkes) Keywords: Trace Metal, Lip, UV-Vis Spectrophotometry